THE UNIQUE MECHANISMS OF THE “PROSPEROUS AND SAFE NEIGHBORHOOD” PRINCIPLE IN CREATING A SAFE ENVIRONMENT - Rakhimov Ilkhomjon Azimjonovich (Western European Studies, 2024)
In the article, the essence of the concept of "Prosperous and safe neighborhood" in New Uzbekistan in recent years, the importance of the "Safe neighborhood" system in the selfmanagement structure, problems of neighborhood residents' preparation for such situations in emergency situations, prevention of crime in neighborhoods It aims to study the concept of "safe neighborhood".
Keywords: prevention; concept; neighborhood; residents